2013
DOI: 10.1177/0143831x13511275
|View full text |Cite
|
Sign up to set email alerts
|

Community organising in the UK: A ‘new’ approach for trade unions?

Abstract: In recent years a number of UK unions have been considering how to (re)engage with communities in order to rebuild the links that were so important to the origins and development of trade unionism. As such, we have seen parts of the UK union movement investing time and resources into exploring whether community organising can engage new actors and new union members in fighting for workers rights and against social injustice more broadly. This paper explores the factors behind this ÔnewÕ turn to community-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 39 publications
0
65
0
2
Order By: Relevance
“…While the potential for creating new discourses and organising to bring about positive social change remains and organisations have sought alternative approaches to express critical voice there was little evidence in the study of mainstream voluntary sector organisations supporting or building new associational social movements , Milbourne and Cushman 2015, Schmid et al 2008.There are problems developing unified voice among disparate communities and the research revealed concerns that austerity is undermining the last resort of welfare provision (Interviewee 5,6,7,8). Alternative discourses have not, so far it appears, emerged that challenge incorporation, reductions in service quality, or project and organisational closures , Holgate 2013. The ability to express critical voice is recognised as a core foundation of civil society (Chaves et al 2004).…”
Section: Discussion Analysis and Conclusion: The Changing Space In mentioning
confidence: 99%
See 1 more Smart Citation
“…While the potential for creating new discourses and organising to bring about positive social change remains and organisations have sought alternative approaches to express critical voice there was little evidence in the study of mainstream voluntary sector organisations supporting or building new associational social movements , Milbourne and Cushman 2015, Schmid et al 2008.There are problems developing unified voice among disparate communities and the research revealed concerns that austerity is undermining the last resort of welfare provision (Interviewee 5,6,7,8). Alternative discourses have not, so far it appears, emerged that challenge incorporation, reductions in service quality, or project and organisational closures , Holgate 2013. The ability to express critical voice is recognised as a core foundation of civil society (Chaves et al 2004).…”
Section: Discussion Analysis and Conclusion: The Changing Space In mentioning
confidence: 99%
“…In response to austerity there has been an increased focus on voluntary action, community organising and community unionism. However, while community organising potentially offers a voice for disadvantaged people and communities this is not unproblematic and there are problems building social movements, developing effective coalitions and overcoming tensions and divisions within broad social movements (Rochester 2013b, McBride and Greenwood 2009, Holgate 2013.…”
Section: Theoretical Framework: the Restructuring Of Welfare And Volumentioning
confidence: 99%
“…A number of writers argue that the interest in union-community alliances reflects awareness that unions are unable to rebuild single-handedly (Holgate, 2015a). Academics have also been interested in how 'new actors' such as these alliances and/or community/civil society organisations may influence the employment relationship (Holgate, 2015a(Holgate, , 2015b by forming effective coalitions (Tattersall, 2010). Wills (2001), however, observes that there is a 'danger in overstating the originality of new efforts to establish' union-community relations and notes that 'trade unions have always had connections with the communities of which they are a part' (p. 481).…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…There is now an elaborate literature on union-community coalitions, with researchers identifying different forms of coalition and the conditions under which they are most likely to prove successful (Tattersall, 2010). The theme of coalition has also featured prominently in more recent work on 'community unionism' (Holgate, 2015). In the context of union organising, coalition with community, faith and social movement organisations can perform a number of different functions.…”
Section: Organising Diversitymentioning
confidence: 99%